Profile Analysis of UCC Employees (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2024)
Employees are the lifeblood of any organization, driving its success and shaping its reputation. Understanding the characteristics and needs of employees is crucial for effective management, resource allocation, and strategic planning. Employee profiling provides a comprehensive overview of the workforce, enabling organizations to make informed decisions that foster employee satisfaction, productivity, and organizational growth.Union Christian College (UCC), a renowned educational institution in San Fernando, La Union, recognizes the importance of employee profiling. A group of office administration students conducted a profiling analysis of 79 UCC teaching and non-teaching personnel to understand its workforce better. Employing a descriptive design, the researchers collected data through a survey questionnaire, ensuring adherence to the institution’s ethical guidelines and standards.The findings of the study revealed several key insights into the UCC workforce: Demographic Profile: Most UCC employees are females, are single, and fall within the 20-25 age bracket. Their basic salary ranges from 10,000 to 15,000 pesos per month. Professional Profile: Most UCC employees are teachers and hold permanent positions. Many have participated in seminars and training programs primarily focused on technological, ethical, and pedagogical skills. However, participation in office management, finances, and resource management training were relatively low. Training Perception: UCC employees value the institution's training opportunities, recognizing their relevance to their professional development. Personnel Development and Profile Factors: No significant relationship between personnel development competence and the identified profile factors was found, suggesting that factors beyond age, gender, marital status, salary, and position influence employee development needs.Based on these findings, the researchers recommended developing a continuous professional development program for teaching and non-teaching personnel. This program should be tailored to address the specific needs of UCC employees, aligning with the institution’s human resource staffing requirements.The employee profiling analysis conducted at UCC highlights the valuable insights gained from understanding the workforce. By recognizing its employees' unique characteristics and needs, UCC can make informed decisions that enhance employee satisfaction, promote professional development, and contribute to its continued success